Geochronological Constraint on the Evolution of the Aktyuz Terrane, Kyrgyz North Tianshan, and the Fate of the Taldybulak Levoberezhny Gold Deposit - Xi, Wei; Li, Nuo; Xia, Xiaohong; Ling, Xiaoxiao; Wu, Yanshuang (Frontiers in Earth Science, 2021)
The Aktyuz Terrane in Kyrgyz North Tianshan is of particular interest due to the occurrence of high and ultrahigh pressure (HP–UHP) rocks and it containing the third largest gold deposit in Kyrgyz North Tianshan, i.e., Taldybulak Levoberezhny (abbreviated to Taldybulak Lev.). To constrain the ages of the host Kemin Complex and its auriferous monzogranite porphyry, detailed zircon U–Pb dating [by laser ablation inductively coupled plasma-mass spectrometry (LA-ICPMS) and secondary ion mass spectroscopy (SIMS)] and Lu–Hf isotopic analyses were carried out. The intensively altered auriferous monzogranite porphyry yielded two weighted mean ages of 444 ± 3 Ma (n = 14, mean squared weighted deviation (MSWD) = 0.49, by LA-ICPMS) and 440 ± 5 Ma (n = 8, MSWD = 0.82, by SIMS) that are indistinguishable within error ranges. Such ages are consistent with a previously reported sulfide Re–Os isochron age of 434 ± 18 Ma, supporting a Silurian porphyry gold mineralization. The granitic gneiss yielded a protolith age of 773 ± 7 Ma (n = 7, MSWD = 0.04) and two metamorphic ages of 514 ± 4 Ma (n = 8, MSWD = 0.09) and 483 ± 3 Ma (n = 11, MSWD = 0.04). Detrital zircons from one fuchsite schist sample yielded highly variable ages from 729 ± 13 Ma to 2,463 ± 30 Ma, with 12 data points weighted at 740 ± 5 Ma (MSWD = 0.95). The metamorphic overgrowth yielded a weighted mean age of 460 ± 4 Ma (n = 4, MSWD = 0.15). Detrital zircons in the migmatitic amphibolite are aged from 788 ± 7 Ma to 3,447 ± 32 Ma, with two major concentrations at 941 ± 7 Ma (n = 13, MSWD = 0.95) and 794 ± 5 Ma (n = 8, MSWD = 0.19). The metamorphic overgrowth yielded an average age of 555 ± 4 Ma (n = 8, MSWD = 0.65). The detrital and xenocryst zircons, and evolved εHf(t) values (−20.9 to −7.8) and old two-stage Hf model ages (1,367–3,159 Ma), revealed the presence of a Precambrian basement that may be dated back to the Archean Eon. The two metamorphic ages may correlate with oceanic subduction and continental collision, respectively.